Implementation of an Employee Acceptance Decision Support System Using the Simple Additive Weighting (SAW) Method at the Musda Perbaungan Private Vocational School - Rajali Limbong (Institute of Computer Science, 2019)
Employee acceptance factors at SMK Private MUSDA Perbaungan the current applies are education, work experience, GPA, age, interview, personality test, field test and work experience, which are considered necessary to improve the quality of educational institutions. In addition, the process of placing application files is still manual so that prospective applicant files must be evaluated by comparing the file contents with the specified criteria. This series of processes is carried out to supplement the material of consideration in determining what to look for will certainly be very time consuming, so that a decision-making system is needed. Thus, a decision support system for employee acceptance is needed. Decision support systems use the SAW method.